Limites e possibilidades da/na gestão do Conselho de Acompanhamento e Controle Social FUNDEF/FUNDEB em Rondonópolis – MT - Caldeira, Rosimeire de Jesus (2016)
This research was based on a case study on the Board of Monitoring and Social Control (CACS) of the public education funding policy, which provides for the Maintenance Fund and Development of Elementary Education and Teaching Enhancement/FUNDEF, and the Maintenance Fund and Development of Basic Education and Enhancement of Education Professional/FUNDEB, on the role played by the city council in the city of Rondonópolis - MT. The research aims to recognize the limits and possibilities presented by the Council of FUNDEF and FUNDEB, monitoring and controlling implementation of financing policies in the educational area of the city of Rondonópolis - MT, from 1998 to 2014. The study was guided by the following question: What are the limits and the possibilities presented to the Council Board of FUNDEF/FUNDEB related to the monitoring and control of the implementation of the educational funding policies in the city of Rondonópolis - MT, from 1998 to 2014? The study focused on the Council Management, in terms of political participation in the processes of composition, organization, operation and performance, thus, from monitoring to social control of the Board, as expressed in the laws that regulate the FUNDEF/FUNDEB. Regarding the research methodology, a qualitative approach was adopted, with the historical-organizational case with Bogdan & Biklen (1994), with a descriptive and interpretive nature, developed through field research. Data was collected through official documents and semi-structured interviews. Document analysis was done under the Cellard (2008) approach, as well as theoretical reference was distributed in the areas of social science, under the names of Kosik (1976), Oliveira (2007), and Demo (1985). The analysis was divided into three blocks: first, the presentation of the location of the research, followed by the discussion of the process of creation and composition of the FUNDEF/FUNDEB in the city; the second part refers to the organization and functioning of the CACS management, and, finally, the performance, limits and possibilities of CACS. Results show the following limitations of CACS FUNDEF/FUNDEB: representativeness, organization, control, participation, dialogue, training, lack of information from the Executive, analysis done by the Council of FUNDEF/FUNDEB, lack of access to documentation of the Fund, lack of conversation between the directors and their bases, autonomy and studying. The data still show that elements like: ordinary meetings, council board involvement, control, and the results report analysis are seen as possibilities in the CACS managing.